The Effect of Top-Level Domains and Advertisements on Health Web Site Credibility - Walther, Joseph B; Wang, Zuoming; Loh, Tracy (Journal of medical Internet research, 2004)
Concerns over health information on the Internet have generated efforts to enhance credibility markers; yet how users actually assess the credibility of online health information is largely unknown. This study set out to (1) establish a parsimonious and valid questionnaire instrument to measure credibility of Internet health information by drawing on various previous measures of source, news, and other credibility scales; and (2) to identify the effects of Web-site domains and advertising on credibility perceptions. Respondents (N = 156) examined one of 12 Web-site mock-ups and completed credibility scales in a 3 x 2 x 2 between-subjects experimental design. Factor analysis and validity checks were used for item reduction, and analysis of variance was employed for hypothesis testing of Web-site features' effects. In an attempt to construct a credibility instrument, three dimensions of credibility (safety, trustworthiness, and dynamism) were retained, reflecting traditional credibility sub-themes, but composed of items from disparate sources. When testing the effect of the presence or absence of advertising on a Web site on credibility, we found that this depends on the site's domain, with a trend for advertisements having deleterious effects on the credibility of sites with .org domain, but positive effects on sites with .com or .edu domains. Health-information Web-site providers should select domains purposefully when they can, especially if they must accept on-site advertising. Credibility perceptions may not be invariant or stable, but rather are sensitive to topic and context. Future research may employ these findings in order to compare other forms of health-information delivery to optimal Web-site features.